Saung Angklung Udjo: Wisata dan Pelestarian Budaya - Susanti, Santi; Sjuchro, Dian Wardiana (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2019)
Introducing traditional art to millennials is not easy, because it requires innovation and the ability to adapt to current conditions. Saung Angklung Udjo (SAU) has succeeded in breaking the boundary through performing arts that are held in Saung as well as in several events at home and abroad. This paper aims to describe the struggle of Udjo Ngalagena to make traditional music known and sought after by the world community and how Saung Angklung can become a cultural tourism destination that has a role in preserving traditional culture. Using the qualitative-fenomenology method, data were obtained through interviews, observations and documents and literature related to Saung Angklung Udjo. Based on data processing results, as a tourist location, SAU has become a cultural tourism destination that introduces the cultural of Sundanese people in the form of art, especially angklung, through performances by children and teenagers accompanied by angklung music. There are also bamboo craft workshops and the Bamboo Crafts Center Shop which provides bamboo handicraft merchandise that visitors can buy. As a cultural preservation area, SAU performs regularly and pass down cultural traditions to children by educating them Sundanese art and angklung traditions for free. The children will perform in the show, given honorariums until given tuition assistance. Saung Angklung was established as Udjo's effort to unite the love of children, traditional arts, flora and fauna, nature, and environment into harmony, which is comfortable to see, hear and feel